Notre-Dame de Paris - Hugo, Victor 1802-1885; Gradassi, Jean 1907-1989 (Paris Pantheon, 1956)
The 'Hunchback of Notre-Dame' or 'Notre-Dame de Paris' is a French Gothic novel by Victor Hugo, published in 1831. It focuses on the unfortunate story of Quasimodo, the Romani street dancer Esmeralda and Quasimodo's guardian the Archdeacon Claude Frollo in 15th-century Paris. All its elements —Renaissance setting, impossible love affairs, marginalized characters— make the work a model of the literary themes of Romanticism.
Keywords: 20th Century (1901-2000); Novel; Paris (France)